(untitled) (Per Musi, 2017)
The central aim here is to share a panorama of ancient Greek music with students and scholars devoted to the field of music, focusing on its cultural relevance in its original context, and, principally, its singularity concerning the fantastic treats attributed to music in the social imaginary of that epoch. Myths and Philosophy are taken into consideration as places of agency of the symbolism of the fantastic, overflowing symbolism, in the realm of narratives about the real, into particularities such as the musical school education, and even into the bizarre, as the stories about musicians’ death. Gods and heroes that are known as musicians and whose mythic narratives illustrate the fantastic are analyzed here. These gods and heroes reveal symbolic dimensions of music in Greek imaginary with results that can be verified in the thought of philosophers as Pythagoras, Plato and Aristotle, as well as in the thought of music theorists, as Damon of Athens, Archytas of Taras and Philolaus of Croton.